Oligonucleotide-directed site-specific integration of high complexity libraries into ssDNA templates - Hale, M. B. (Oxford University Press, 2004)
We present an approach that generates an oligomer-based library with minimal need for restriction site modification of sequences in the target vector. The technique has the advantage that it can be applied for generating peptide aptamer libraries at sites within proteins without the need for introducing flanking enzyme sites. As an example we present a phagemid retroviral shuttle vector that can be used to achieve stable expression of the library in mammalian cells for the purpose of screening for peptides with desired biological activity.